Uncovering Maria Edgeworth’s Strategic Political Influence Through Her Unpublished Letters - Autumn G. Hall (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2025)
Maria Edgeworth (1768-1849) was one of the most prolific Anglo-Irish novelists of the eighteenth and nineteenth centuries. While Edgeworth’s novels are regularly discussed among Regency-era scholars, researchers have rarely considered her letters and correspondence, especially in relation to her role in contemporary politics. During my time on the Maria Edgeworth Letters Project team, I researched Edgeworth’s previously unpublished letters, which provided a unique view of her strategic political correspondence network. Through her writing, Edgeworth was able to voice her thoughts while also remaining publicly complacent with restrictive societal norms imposed on women. In my article, I argue that through her careful use of reason in her letters, Edgeworth was also able to persuade her male correspondents to consider her political ideas, especially in the case of her interactions with British Whig politician Thomas Spring-Rice, who in turn connected her to figures such as Prime Minister Henry John Temple.
Keywords: Maria Edgeworth; Mary Wollstonecraft; Regency era; Enlightenment era; Proto-Feminist; Novels; Letters; Politics; Women Writers